Complementary Activities of Host Defence Peptides and Antibiotics in Combating Antimicrobial Resistant Bacteria - Patrick R. Lennard; Pieter S. Hiemstra; Peter H. Nibbering (MDPI AG, 2023)
Due to their ability to eliminate antimicrobial resistant (AMR) bacteria and to modulate the immune response, host defence peptides (HDPs) hold great promise for the clinical treatment of bacterial infections. Whereas monotherapy with HDPs is not likely to become an effective first-line treatment, combinations of such peptides with antibiotics can potentially provide a path to future therapies for AMR infections. Therefore, we critically reviewed the recent literature regarding the antibacterial activity of combinations of HDPs and antibiotics against AMR bacteria and the approaches taken in these studies. Of the 86 studies compiled, 56 featured a formal assessment of synergy between agents. Of the combinations assessed, synergistic and additive interactions between HDPs and antibiotics amounted to 84.9% of the records, while indifferent and antagonistic interactions accounted for 15.1%. Penicillin, aminoglycoside, fluoro/quinolone, and glycopeptide antibiotic classes were the most frequently documented as interacting with HDPs, and Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Enterococcus faecium were the most reported bacterial species. Few studies formally evaluated the effects of combinations of HDPs and antibiotics on bacteria, and even fewer assessed such combinations against bacteria within biofilms, in animal models, or in advanced tissue infection models. Despite the biases of the current literature, the studies suggest that effective combinations of HDPs and antibiotics hold promise for the future treatment of infections caused by AMR bacteria.